VISUALIZATION OF NATURAL TOURISM IN LIMA PULUH KOTA DISTRICT USING INFOGRAPHIC ANIMATION MEDIA - Robby Usman; Tito -; Aulia Fitrul Hadi (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
Fifty Cities Regency has a lot of natural tourism potential. However, there are still many of these Nature Tourism that are not exposed and are not paid attention by the government, as well as the lack of information obtained by the public about Fifty Cities Tourism Objects. This research provides information media and promotion of Nature Tourism in Fifty Cities District through Two-Dimensional Visualization Animation. This Animated Visualization of Nature Tourism in Fifty Cities Regency was developed using infographic animation techniques which were arranged through pre-production, production and post-production stages. The final result of this animation is expected to be able to help the government to promote and introduce Fifty Cities District Nature Tourism to the local community. and proven to increase the prestige of tourism by 66,8%.